ANALISIS PENDAPATAN, KELAYAKAN FINANSIAL DAN STRATEGI PEMASARAN USAHATANI JAMBU METE DI DESA MASUMELI KECAMATAN SOA KABUPATEN NGADA - Maria Sherlina Eno Wale; Charles Kapioru; Ayu Fitriani (Kybernology Jurnal Ilmu Pemerintahan dan Administrasi Publik, 2026)
Cashew nut farming is one of the leading plantation commodities in Ngada Regency with the potential to improve the economic welfare of the community; however, farmers are still faced with price fluctuations and limitations in product downstreaming. This research was conducted in Masumeli Village, Soa District, Ngada Regency. The aims of this study were to: (1) determine cashew nut farming income, (2) assess the financial feasibility of cashew nut farming, and (3) identify the appropriate marketing strategy for cashew nut farming development in the area. The study was conducted purposively with a sample size of 30 respondents selected from a total population of 120 cashew nut farmer households. Data were analyzed using income analysis, financial feasibility analysis with investment criteria of Net Present Value (NPV), Internal Rate of Return (IRR), and Net Benefit-Cost Ratio (Net B/C) at a 12% sensitivity interest rate, as well as SWOT matrix analysis to formulate the marketing strategy. The results showed that the average net income of cashew nut farming was IDR 9,696,581 per farmer/year or IDR 15,230,236 per hectare/year, with a total revenue of IDR 10,723,333 per farmer/year and IDR 16,842,932 per hectare/year. Cashew nut production reached 714.89 kg per farmer/year or 1,122.85 kg per hectare/year. The financial feasibility analysis empirically demonstrated a positive NPV of IDR 31,395,300 (NPV > 0), an IRR of 42.33% (IRR > 12%), and a Net B/C Ratio of 1.86, indicating that cashew nut farming is highly feasible for long-term development. The SWOT analysis indicated that the business position is in Quadrant I with an aggressive strategic recommendation (Strength-Opportunity), which entails maximizing internal strengths to capture market opportunities through increasing production continuity, accelerating the downstreaming of processed post-harvest cashew products to add value, and optimizing farmer group institutions to strengthen farmers' bargaining power against middlemen.